Solvent-dependent aggregation behavior of a new Ru(ii)-polypyridyl based metallosurfactant - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chemical Communications, 2011)
Variation of the solvent polarity leads to the formation of vesicles and reverse vesicles of a newly synthesized amphiphilic Ru(II)-polypyridyl complex.

Self-assembly of modified rhodamine-6G with tri-block copolymer: unusual vesicles formation, pH sensing and dye release properties - Praveen, L.; Saha, Sukdeb; Jewrajka, Suresh K.; Das, Amitava (Journal of Materials Chemistry B, 2013)
A new rhodamine-6G derivative having a C18-alkyl chain self-assembles with an amphiphilic tri-block copolymer and forms stable vesicles in water or in water–ethanol (4 : 1, v/v) medium. The stability of the spirolactam form of the rhodamine-6G derivative in these vesicular structures, along with studies of controlled dye release and pH sensing are discussed. Transmission electron micrographs and DLS analyses confirm the formation of vesicular structures. Atomic force microscopy (AFM) images show that the self assembled tri-block copolymer-octadecyl rhodamine vesicles form near spherical nanostructures with a size ranging from 80 to 110 nm. Furthermore, the vesicular system is disassembled under acidic conditions, releasing the cargo which are an integral part of the vesicle. Dye-release studies showed that the release rates of the loaded dye in the vesicles could be well-controlled as a function of the media pH. These results offer an opportunity to use these nanovesicles as imaging reagents for probing media pH with their simultaneous use as nanocarriers for intracellular drug delivery.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).